1997
DOI: 10.2307/3054043
|View full text |Cite
|
Sign up to set email alerts
|

Cause Lawyering in Transnational Perspective: National Conflict and Human Rights in Israel/Palestine

Abstract: There is an interest among scholars working on cause lawyering to “globalize” the subject by studying professional and political networks that span national boundaries. The globalizing scope of human rights provides a particularly relevant perspective, complementing the more narrowly attenuated focus on the roles and activities of cause lawyers. The subjects of this article are Israeli and Palestinian cause lawyers who have worked in the Israeli military court system in the Occupied Territories. This study ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Generally, there are a number of civil rights organizations who are involved in litigation in Israeli courts on behalf of Palestinians. Some of these organizations do have practices of carefully screening the cases that they take (Hajjar 1996;Dotan 1999). In our study, however, we found only five cases in which the petitioners' lawyers acted on behalf of civil rights organizations during the research period.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Generally, there are a number of civil rights organizations who are involved in litigation in Israeli courts on behalf of Palestinians. Some of these organizations do have practices of carefully screening the cases that they take (Hajjar 1996;Dotan 1999). In our study, however, we found only five cases in which the petitioners' lawyers acted on behalf of civil rights organizations during the research period.…”
Section: Discussionmentioning
confidence: 59%
“…The eight lawyers included in the political group were involved in 100 out of 134 cases in the study. More generally, cause lawyers (and civil rights organizations) are heavily involved in litigation on behalf of Palestinians before Israeli courts (Hajjar 1996;Dotan 1999). The intensive involvement of such lawyers in this field may improve the effectiveness in more than one way: First, it can simply account for professional specialization and expertise in the relevant legal field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelly (2006), echoing Hajjar (1997), shows how the continuing dominance of military governance in the lives of West Bank Palestinians since Oslo ''means that their relationships with public officials are predominately those of subjects rather than citizens'' (ibid, p. 13). Kelly's book describes six labor disputes in detail, collected during 18 months of fieldwork from the summer of 2000 to the spring of 2002, in a village in the Ramallah District.…”
mentioning
confidence: 94%